2018
DOI: 10.1002/ajb2.1133
|View full text |Cite
|
Sign up to set email alerts
|

Shedding new light on the origin and spread of the brinjal eggplant (Solanum melongena L.) and its wild relatives

Abstract: Rather than a linear 'Out Of Africa' sequence, our results are more consistent with an initial dispersal event into Asia, and subsequent wide dispersal and differentiation across Africa driven by large mammalian herbivores. Our evolutionary results will affect future work on eggplant domestication and affect the use of wild relatives in breeding of this increasingly important solanaceous crop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 66 publications
0
37
0
Order By: Relevance
“…It has been shown that plastid genome based "super barcoding" could overcome these difficulties and could differentiate species in difficult taxonomic groups. This approach has been successfully employed in the S. melongena complex to trace the ancestors of cultivated eggplant and differentiate closely related wild species [98]. Here, we compared the complete plastome sequences of four Withania species and investigated if plastid genomes based "super barcoding" could be applied among closely related ashwagandha species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that plastid genome based "super barcoding" could overcome these difficulties and could differentiate species in difficult taxonomic groups. This approach has been successfully employed in the S. melongena complex to trace the ancestors of cultivated eggplant and differentiate closely related wild species [98]. Here, we compared the complete plastome sequences of four Withania species and investigated if plastid genomes based "super barcoding" could be applied among closely related ashwagandha species.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that DNA barcoding can fail in complicated groups [ 96 ]. Solanaceae includes many species complexes with tangled taxonomy such examples of species groups can be found in potatoes and its wild relatives, e.g., Solanum brevicaule complex [ 97 ], or the eggplant and its wild relatives ( S. melongena complex [ 98 ]) but in other clades of the family for example in the genus Petunia [ 99 ] or closely related Physalis [ 100 ]. In these complicated groups well known plastid barcode regions (e.g., trn H- psb A, mat K) could lack enough polymorphism and thus could fail to provide species-specific information necessary for differentiation [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Staats et al (2011) showed that it is also possible to use genome skimming to analyze DNA that is otherwise too degraded for PCR-based approaches, thus offering the possibility to include rare and extinct species from natural history collections in phylogenetic analyses. Several phylogenomic studies have explored the potential of herbarium specimens of different ages (Staats et al, 2013; Besnard et al, 2014; Aubriot et al, 2018; McManus et al, 2018; Zeng et al, 2018). For example, the entire nuclear genome of a 43-year-old Arabidopsis thaliana (L.) Heynh.…”
Section: Introductionmentioning
confidence: 99%
“…Pre-dispersal defense via secondary chemistry among Australian species with non-accrescent calyces was proposed by Symon [3], and has been well-studied in other Solanum clades (e.g. [11,13,14,47]), with green striping on fruits produced by most of the non-accrescent species presumed to be both a warning signal and a camouflage via cryptic coloration against green foliage (Fig 1H).…”
Section: Discussionmentioning
confidence: 93%